Clinico-pathological features of the drug reaction with eosinophilia and systemic Symptoms syndrome: A case study - Nagarajan, Sowmya; N S, Harsha; Jagadeesh, Sneha; K S, Deepak; S Pujar, Yeshaswini (Eastern Journal of Medical Sciences, 2021)
Drug reaction with eosinophilia and systemic symptoms syndrome is a syndrome with a varied spectrum of clinical features. The cutaneous manifestations can be an urticarial, maculopapular eruption also including, vesicles, bullae, pustules, purpura, target lesions, facial edema, cheilitis, and erythroderma. Systemic manifestations include lymphadenopathy, fever, and leukocytosis (often with eosinophilia or atypical lymphocytosis), as well as hepatitis, nephritis, pneumonitis, myositis, and gastroenteritis, in descending order. Diagnosis can be made on the basis of the clinical picture and the RegiSCAR (Registry of Severe Cutaneous Adverse Reaction group) scoring system. Here, we present the case of a 40-year-old male with a history of herbal medicine intake after which he developed a diffuse skin rash.